Pengaruh Profitabilitas, Kepemilikan Institusional dan Financial Leverage terhadap Praktik Manajemen Laba pada Perusahaan Manufaktur Sub Sektor Farmasi - Cindy Olivia Tanisia; Jenny Morasa; Heince R.N. Wokas (Syntax Corporation, 2023)
This study aims to determine and analize the effect of profitability, institutional ownership, and financial leverage on earnings management practices in pharmaceutical sub sector manufacturing companies listed on the Indonesian Stock Exchange (IDX) for the 2015-2021 period. The data in this study are 56 data, namely 7 years of time series data and 8 companies. The data analysis used in this study is multiple regression. The results of the study show that (1) Profitability (Return on Assets) has a positive and significant effect on earnings management practices in Manufacturing Companies in the Pharmaceutical Sub Sector Listed on the Indonesia Stock Exchange (IDX) for the 2015-2021 period. (2) Institutional ownership has a significant negative effect on earnings management practices in Manufacturing Companies in the Pharmaceutical Sub Sector Listed on the Indonesia Stock Exchange (IDX) for the 2015-2021 period. (3) Financial Leverage (Debt to Asset ratio) has no significant positive effect on earnings management practices in Manufacturing Companies in the Pharmaceutical Sub Sector Listed on the Indonesia Stock Exchange (IDX) for the 2015-2021 period.